European modernism and the information society : - [edited by] by W. Boyd Rayward. (Ashgate)
Introduction: European modernism and the information society : conceptual interdependence / W. Boyd Rayward -- Understanding the information domain : the uneasy relations between sociology and cultural studies and the peculiar absence of history / Frank Webster -- On the cultural and intellectual context of European documentation in the early twentieth century / Michael Buckland -- A tale of two narratives : prolegomena to an alternative history of library and information science / Steve Fuller -- The role of facts in Paul Otlet's modernist project of documentation / Bernd Frohmann -- Ferdinand Vander Haeghen's shadow on Otlet : European resistance to the Americanized modernism of the Office international de bibliographie / Pieter Uyttenhove and Sylvia Van Peteghem -- Towers and globes : architectural and epistemological differences between Patrick Geddes's Outlook towers and Paul Otlet's Mundaneums / Pierre Chabard -- Building society, constructing knowledge, weaving the web : Otlet's visualizations of a global information society and his concept of a universal civilization / Charles van den Heuvel -- Networking knowledge before the information society : the Manchester Central Library (1934) and the metaphysical-professional philosophy of L.S. Jast / Alistair Black -- Documentation and utopia : Fabian anticipations of the information society / Alistair S. Duff -- Public science in Britain and the origins of documentation and information science, 1890-1950 / Dave Muddiman -- The march of the modern and the reconstitution of the world's knowledge apparatus : H.G. Wells, encyclopedism, and the world brain / W. Boyd Rayward -- The modern museum in the age of its mechanical reproducibility : Otto Neurath and the Museum of Society and Economy in Vienna / Nader Vossoughian -- Gesellschaft und wirtschaft : an encyclopedia in Otto Neurath's pictorial statistics from 1930 / Sybilla Nikolow -- Visualizing social facts : Otto Neurath's isotype project / Frank Hartmann -- Paper parasite : F.M. Feldhaus and the historiography of technology / Markus Krajewski -- Roots of mediating information : aspects of the German information movement / Thomas Hapke.